064 Parkinson's disease and the gastrointestinal microbiome: clinicopathological correlations and controversies. (29th July 2019) - Lubomski, Michal; Tan, Ai Huey; Lim, Shen-Yang; Holmes, Andrew; Davis, Ryan L; Sue, Carolyn M
Abstract : Introduction: There has been a recent surge in interest around the gastrointestinal microbiome (GM) and its association with Parkinson's disease (PD). The GM mediates interactions between the brain and the gut via the 'microbiota-gut-brain-axis'. Compelling studies suggest that a shift in GM composition may play an important role in the pathogenesis and progression of PD. Methods: We conducted a literature review exploring the pathological association between the GM, α-synuclein spread and intestinal inflammation in PD. We also summarised patterns and correlations of gut microflora seen in clinical studies of the GM in PD. Results: To date 14 mainly cross-sectional studies from 7 countries have reported GM alterations in PD. All studies described significant alterations between PD and healthy control groups across multiple bacterial families, genera and species. Several studies suggested that putative 'pro-inflammatory' bacteria were significantly more abundant, while putative beneficial bacteria were less abundant in PD. Various complex microbiota-gut-brain-axis interactions have been proposed due to alterations in the GM, inferred by changes in gut mucosal integrity and permeability, short-chain-fatty-acid metabolism, oxidative stress and inflammation. Conclusions: Across the recent GM studies in PD, alterations in bacterial taxa have been repeatedly associated with various clinicopathological features, endorsing a plausible biological link between the GM and PD. Mechanisms involved in the pathogenesis of PD due to GM changes are complex and require ongoing study.